EVALUASI ANGKA KEBUTUHAN NYATA OPERASIONAL DAN PEMELIHARAAN BANGUNAN PENGENDALI SEDIMEN DI SUNGAI POHU - Abaidata, Riton (Gorontalo Journal of Infrastructure and Science Engineering, 2023)
This research was carried out on a sediment control building on the Pohu River, Gorontalo Regency, Gorontalo Province, using the method in the Guidelines for the Implementation of Operation and Maintenance Activities for River Infrastructure and River Maintenance in accordance with the Circular Letter of the Directorate General of Water Resources, Ministry of Public Works and Public Housing. River performance assessment is a pressing issue in Indonesia that faces many challenges. Therefore, appropriate treatment is needed to determine indicators of the level of river management in order to manage and repair the river before permanent damage occurs. The research carried out was located on the Pohu River in the Limboto Watershed. The research method was carried out using descriptive analysis by collecting primary data in the form of assessing the performance of sediment control buildings in the Pohu watershed. Apart from that, this research analyzed the morphology of the Pohu River using the ArcGIS application. The research results show that the morphology of the Pohu River is vulnerable to a reduction in vegetation land cover and has the potential to provide increased sedimentation transport every year. The ability of the Pohu River sediment management building has also experienced a significant impact, which then needs to be maintained on an ongoing basis.Penelitian ini dilakukan pada bangunan pengendali sedimen di Sungai Pohu Kabupaten Gorontalo Provinsi Gorontalo dengan menggunakan Metode pada Pedoman Penyelenggaraan Kegiatan Operasi dan Pemeliharaan Prasarana Sungai Serta Pemeliharaan Sungai sesuai Surat Edaran Direktorat Jendral Sumber Daya Air Kementerian Pekerjaan Umum dan Perumahan Rakyat. Penilaian kinerja sungai merupakan masalah yang mendesak di Indonesia yang menghadapi banyak tantangan. Oleh karena itu diperlukan sebuah penanganan yang tepat untuk mengetahui indikator tingkat penanganan sungai untuk melakukan pengelolaan dan perbaikan sungai sebelum terjadinya kerusakan secara permanen. Penelitian yang dilakukan terletak di Sungai Pohu DAS Limboto. Metode penelitian dilaksanakan dengan analisis deskriptif dengan pengambilan data primer berupa penilaian kinerja bangunan pengendali sedimen pada DAS Pohu. Selain itu pada penelitian ini menganalisis morfologi sungai pohu menggunakan aplikasi Arc GIS. Hasil penelitian menunjukan bahwa morfologi sungai pohu rentan terhadap pengurangan tutupan vegetasi lahan dan berpotensi memberikan angkutan sedimentasi yang meningkat setiap tahunnya. Kemampuan bangunan pengendali sedimen sungai pohu pun mengalami dampak yang signifikan yang kemudian perlu dipelihara secara berkelanjutan.